PELATIHAN PENINGKATAN KOMPETENSI GURU WIDYALAYA MELALUI PENDEKATAN PEMBELAJARAN DEEP LEARNING DI KABUPATEN BADUNG - Anggreni, Putri (UNHI Press, 2025)
This Community Service Activity (PkM) aims to improve the pedagogical competence of Widyalaya teachers in Badung Regency through understanding and implementing the deep learning approach in the learning process. This activity is motivated by the low level of understanding among Widyalaya teachers regarding the concept of deep learning. The implementation of the activity employs a Service Learning approach combined with Participatory Action Research and Community-Based Research, enabling educational interaction between the service team and teachers as participants. The activity was conducted in the form of face-to-face training and simulations of deep learning-based lesson planning. The conclusion of this activity state that training.